The Integration and Development of Piano Art and Media Education and Its Influence on the Long-Term Care and Happiness of the Elderly People - Chen, Xuan; Huang, Fangwei; Wang, Yingfeng (Frontiers in Psychology, 2021)
In order to promote the integration and development of piano art and media education in the new era for the elderly in today's aging society and improve their later life in the new media era, a questionnaire is used to make an empirical analysis on the happiness of the elderly in an aging society through the integration and development of piano art and media education in the new media era. First of all, the development characteristics of piano art in the new media era, the integration of piano culture and art, the change of the communication form of piano art by new media, and the relationship between piano art and the elderly people in the new media era are introduced. Then the factors influencing the long-term care and subjective well-being of the elderly under the background of the integration and development of piano art and media education are analyzed. Finally, the mechanism of the integration and development of piano art and media education on the long-term care and happiness of the elderly is summarized. The results showed that the learning process of piano art could improve the subjective well-being of the grey-haired people. In addition, the elderly who have been exposed to piano art for a long time are more active in life. Piano art edification is an important factor affecting the psychological well-being of the silver people. The research has a good guiding significance for improving the happiness of the elderly.